Antigen-specific T cell recognition of affinity-purified and recombinant thyroid peroxidase in autoimmune thyroid disease. - Ewins, D L (1992)
The T cell proliferative responses of peripheral blood lymphocytes from 20 patients with autoimmune thyroid disease (AITD) and 20 healthy controls were analysed to immunoaffinity-purified thyroid peroxidase (TPO) and recombinant antigen preparations generated in Escherichia coli as glutathione-s-transferase fusion proteins. The epitope specificity of the T cell response was investigated using a selection of eight discrete recombinant fragments encompassing the whole of the extracellular region of the TPO molecule. Significant differences in the proliferative responses between patients and controls were observed to the full length, affinity-purified TPO molecule (P less than 0.002) as well as to the recombinant fragments R1c (residues 145-250) (P less than 0.001) and R2b (residues 457-589) (P less than 0.001) suggesting the presence of at least two distinct T cell determinants on this autoantigen. One of these T cell epitopes, localized within the region R1c, has not previously been identified by studies with synthetic peptides.